High Frequency of CD8 Positive Lymphocyte Infiltration Correlates with Lack of Lymph Node Involvement in Early Rectal Cancer. (30th December 2014) - Däster, Silvio; Eppenberger-Castori, Serenella; Hirt, Christian; Zlobec, Inti; Delko, Tarik; Nebiker, Christian A.; Soysal, Savas D.; Amicarella, Francesca; Iezzi, Giandomenica; Sconocchia, Giuseppe; Heberer, Michael; Lugli, Alessandro; et al.
Abstract : Aims . A trend towards local excision of early rectal cancers has prompted us to investigate if immunoprofiling might help in predicting lymph node involvement in this subgroup. Methods . A tissue microarray of 126 biopsies of early rectal cancer (T1 and T2) was stained for several immunomarkers of the innate and the adaptive immune response. Patients' survival and nodal status were analyzed and correlated with infiltration of the different immune cells. Results . Of all tested markers, only CD8 (P = 0.005 ) and TIA-1 (P = 0.05 ) were significantly more frequently detectable in early rectal cancer biopsies of node negative as compared to node positive patients. Although these two immunomarkers did not display prognostic effect "per se, " CD8+ and, marginally, TIA-1 T cell infiltration could predict nodal involvement in univariate logistic regression analysis (OR 0.994; 95% CI 0.992–0.996; P = 0.009 and OR 0.988; 95% CI 0.984–0.994; P = 0.05, resp.). An algorithm significantly predicting the nodal status in early rectal cancer based on CD8 together with vascular invasion and tumor border configuration could be calculated (P < 0.00001 ). Conclusion . Our data indicate that in early rectal cancers absence of CD8+ T-cell infiltration helps in predicting patients' nodal involvement.